2009
DOI: 10.1104/pp.109.150854
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Sucrose Uptake Capacity of Wheat Grains Stimulates Storage Protein Synthesis  

Abstract: Increasing grain sink strength by improving assimilate uptake capacity could be a promising approach toward getting higher yield. The barley (Hordeum vulgare) sucrose transporter HvSUT1 (SUT) was expressed under control of the endosperm-specific Hordein B1 promoter (HO). Compared with the wild type, transgenic HOSUT grains take up more sucrose (Suc) in vitro, showing that the transgene is functional. Grain Suc levels are not altered, indicating that Suc fluxes are influenced rather than steady-state levels. HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
82
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 73 publications
3
82
0
1
Order By: Relevance
“…Takahashi et al (2003) found that seeds of globulin ''null mutants'' of soybean strongly accumulated amino acids, suggesting efficient uptake of amino acids independently of globulin biosynthesis. Grain storage protein (hordein) synthesis seem to be dependent on the available N in the grain as it is demonstrated in several plants by several authors (Balconi et al 1991;Golombek et al 2001;Miranda et al 2001;Rolletschek et al 2005;Weichert et al 2010). It appeared, thus, that other transport mechanisms such as transport (active transport) via specific amino acid transporters against the concentration gradient might hence play a role in the transport and acquisition of amino acids by the developing grains (Patrick 1997;Miranda et al 2001;Williams and Miller 2001;Takahashi et al 2003;Rolletschek et al 2005;Tislner et al 2005).…”
Section: Discussionmentioning
confidence: 91%
“…Takahashi et al (2003) found that seeds of globulin ''null mutants'' of soybean strongly accumulated amino acids, suggesting efficient uptake of amino acids independently of globulin biosynthesis. Grain storage protein (hordein) synthesis seem to be dependent on the available N in the grain as it is demonstrated in several plants by several authors (Balconi et al 1991;Golombek et al 2001;Miranda et al 2001;Rolletschek et al 2005;Weichert et al 2010). It appeared, thus, that other transport mechanisms such as transport (active transport) via specific amino acid transporters against the concentration gradient might hence play a role in the transport and acquisition of amino acids by the developing grains (Patrick 1997;Miranda et al 2001;Williams and Miller 2001;Takahashi et al 2003;Rolletschek et al 2005;Tislner et al 2005).…”
Section: Discussionmentioning
confidence: 91%
“…For example, seed-specific overexpression of a potato (Solanum tuberosum) SUT increased Suc uptake and growth rates of developing pea (Pisum sativum) cotyledons (Rosche et al, 2002). In addition, the Suc uptake capacity of grains and storage protein biosynthesis was increased in transgenic wheat (Triticum aestivum) plants expressing the barley (Hordeum vulgare) SUT HvSUT1 under the control of an endosperm-specific promoter (Weichert et al, 2010). Moreover, it was recently found that these transgenic wheat plants had a higher thousand grain weight and grain width and length, as well as a 28% increase in grain yield (Saalbach et al, 2014).…”
mentioning
confidence: 99%
“…With respect to ectopic expression of SUT genes to study the impact on carbon partitioning, constitutive expression of SoSUT1 (type I) of spinach (Spinacia oleracea) from the Cauliflower mosaic virus 35S promoter in potato (Solanum tuberosum) resulted in shifts in metabolite levels with little effect on tuber morphology (Leggewie et al, 2003), while OE of OsSUT5Z (type IIB) and OsSUT2M (type III) of rice (Oryza sativa) from a tuber-specific promoter was reported to increase tuber yield (Sun et al, 2011). In other species, ectopic expression of potato StSUT1 in the storage parenchyma of pea (Pisum sativum) cotyledons during seed development enhanced Suc influx and enhanced cotyledon growth rates (Rosche et al, 2002), and ectopic SUT expression in wheat (Triticum aestivum) grains increased levels of storage protein, indicating that enhanced Suc transport has benefits beyond carbohydrate accumulation (Weichert et al, 2010).…”
mentioning
confidence: 99%